Accuracy of Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) Score System as An Early Diagnostic Predictor of Necrotizing Fasciitis in A Tertiary Referral Hospital in Bandung, Indonesia - Djajakusumah, Teguh Marfen; Septrina, Rani; Dwinanda, Arief (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: Necrotizing fasciitis (NF) is a serious infection that can rapidly kill tissue and potentially lead to multiple organ failure. Early diagnosis and treatment are essential for survival. The laboratory risk indicator for necrotizing fasciitis (LRINEC) score may aid in early detection of NF. Although initially promising, studies on the effectiveness of LRINEC have shown mixed results. This study aimed to investigate the accuracy of LRINEC in predicting NF.Methods: This was an observational prospective cohort study, including patients with NF as well as skin and soft tissue infection (SSTI) who were treated at a tertiary referral hospital in Bandung, Indonesia in 2022. The LRINEC scores was calculated to measure sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). The accuracy of LRINEC scores was specified in the area under the curve (AUC) of the receiver operating characteristic (ROC) curve. Results: Of the total 70 patients, 33 were diagnosed with NF and 37 with SSTI. The LRINEC score with ≥6 points cut-off showed a sensitivity of 90.9% (95%CI; 75.67–98.08%), specificity of 75.60% (95%CI; 58.80–88.23%), PPV of 76.9% (95%CI; 60.67–88.87%), and NPV 90.30% (95%CI; 74.25–97.96%). The area under the ROC (AUROC) curve for the accuracy of the LRINEC scores was 0.895 (95%CI; 0.821–0.969).Conclusions: The laboratory risk indicator for necrotizing fasciitis (LRINEC) score is an accurate predictor and feasible early diagnostic indicator in NF. However, clinical judgment remains a crucial factor in diagnosing NF.